Normal Form for the 1:1 Resonance Problems for Delayed Reaction-Diffusion Systems (Journal of Nonlinear Modeling and Analysis, 2025)
This article presents a direct method for calculating the normalform coefficients of a 1:1 resonant Hopf bifurcation in reaction-diffusion systems with time delay and Neumann boundary conditions. The formulas obtained in this paper can be easily implemented using a computer algebra system such as Maple or Mathematica.
Keywords: Normal form; 1:1 resonance; Hopf bifurcation; delayed reaction-diffusion.